2021
DOI: 10.1111/ijcs.12693
|View full text |Cite
|
Sign up to set email alerts
|

Being an ethical or unethical consumer in response to social exclusion: The role of control, belongingness and self‐esteem

Abstract: Social exclusion threatens control, belongingness and self‐esteem, and such threats may produce distinct behavioural intentions. This study hypothesized that thwarted control would increase the intention towards unethical consumer behaviour. Additionally, it hypothesized that inhibiting belongingness and self‐esteem would decrease the intention to engage in unethical consumer behaviour for reconnection. To test the hypotheses, we conducted two online experiments, with 117 (63 females and 54 males) and 188 (91 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 117 publications
(235 reference statements)
1
11
0
Order By: Relevance
“…Aghakhani and Main (2019); Baek et al (2018); Baek et al (2019); Bozkurt and Gligor (2019); Chen et al (2017); Dommer et al (2013); Duclos et al (2013); El Hazzouri et al (2017); Gao and Mattila (2016); Guèvremont and Grohmann (2016); Han et al (2015); Hu et al (2018); Jiang et al (2018); Jiang et al (2020); Jiao and Wang (2018); Kandaurova and Lee (2019); Khalifa and Shukla (2017); Kim, Park, et al (2020); Lee et al (2017); Lee and Shrum (2012); Liang et al (2018); Liang and Chang (2016); Liu et al (2021); Loveland et al (2010); Lu and Sinha (2017); Mead et al (2011); Mourey et al (2017); Newman et al (2019); Sinha and Lu (2019); Sinha and Wang (2013); Su et al (2017); Su et al (2019); Tezer and Bodur (2020); Thomas and Saenger (2020); Tunçel and Kavak (n.d.); Vinuales and Thomas (2021); Wan et al (2014); Wang et al (2012); Wang and Ding (2017); Wang and Lalwani (2019); Ward and Dahl (2014); Wu and Dodoo (2020); Xie, Chen and Guo (2020); Xu and Jin (2020); Yang et al (2020); Yi et al (2017)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aghakhani and Main (2019); Baek et al (2018); Baek et al (2019); Bozkurt and Gligor (2019); Chen et al (2017); Dommer et al (2013); Duclos et al (2013); El Hazzouri et al (2017); Gao and Mattila (2016); Guèvremont and Grohmann (2016); Han et al (2015); Hu et al (2018); Jiang et al (2018); Jiang et al (2020); Jiao and Wang (2018); Kandaurova and Lee (2019); Khalifa and Shukla (2017); Kim, Park, et al (2020); Lee et al (2017); Lee and Shrum (2012); Liang et al (2018); Liang and Chang (2016); Liu et al (2021); Loveland et al (2010); Lu and Sinha (2017); Mead et al (2011); Mourey et al (2017); Newman et al (2019); Sinha and Lu (2019); Sinha and Wang (2013); Su et al (2017); Su et al (2019); Tezer and Bodur (2020); Thomas and Saenger (2020); Tunçel and Kavak (n.d.); Vinuales and Thomas (2021); Wan et al (2014); Wang et al (2012); Wang and Ding (2017); Wang and Lalwani (2019); Ward and Dahl (2014); Wu and Dodoo (2020); Xie, Chen and Guo (2020); Xu and Jin (2020); Yang et al (2020); Yi et al (2017)…”
Section: Methodsmentioning
confidence: 99%
“…Excluded individuals are more likely to evaluate the perpetrators of rejection negatively (Twenge et al, 2001), engage in aggressive behaviour (Gabbiadini and Riva, 2018; Reiter‐Scheidl et al, 2018), and extend less help to others (Chung, 2018; Twenge et al, 2007). Exclusionary experiences deplete one's sense of control, thereby increasing one's intention to engage in unethical consumption behaviour (Tunçel & Kavak, n.d.). Ostracism by cooperatives, which thrive on the mutual relationship between customer–member, may result in member–customers' hostile responses (Poon et al, 2013), such as consumers' intention of withdrawing their membership (Benos et al, 2018).…”
Section: A Comprehensive Frameworkmentioning
confidence: 99%
“…Another purpose of Experiment 2 was to test ostracism as an alternative explanation for our findings on loneliness. Other research on consumer behavior has focused on social exclusion (not loneliness), which is most often operationalized through ostracism (Duclos et al, 2013 ; Lu & Sinha, 2017 ; Tunçel & Kavak, 2021 ; Ward & Dahl, 2014 ). Prior research has suggested that ostracized people and lonely people engage in different behavioral patterns.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, those who are lonely are more pessimistic and less eager to participate in social interactions (Cacioppo et al, 2006). Furthermore, ostracism serves as an antecedent to a loneliness, but it often takes time and multiple sequences of rejection for the effects of loneliness to appear (Rawat et al, 2022); thus, one can be rejected and experience a decrease in self‐esteem (Tunçel & Kavak, 2021) but not feel lonely, especially if given the opportunity to reaffiliate with the group following an experience of ostracism (Asher & Weeks, 2014). Therefore, we do not predict that ostracism will serve as an alternative explanation for our findings.…”
Section: Methodsmentioning
confidence: 99%
“…Customer transgressions have been present since the dawn of time (Li et al., 2018; Tunçel & Kavak, 2021; Yang et al., 2017). As the retailing landscape has migrated significantly to the online environment (Anesbury et al., 2016; Davydenko & Peetz, 2020; Yap et al., 2021), the complexity of such transgressions has profoundly increased (Garnefeld et al., 2019; Robertson et al., 2020; Wu, Xu, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%